Lo schiavo al museo. Spunti di riflessione sul trattamento dei temi di schiavitù e tratta atlantica nei musei della Francia metropolitana (Altre Modernità, 2019)
The theme of contemporary slavery is necessarily linked to the history of slavery, especially as a part of former colonialist countries’ past (and identity). It is therefore particularly relevant to consider how public memory represents "historical" slavery through moments of commemoration, speeches, books, monuments and museums. This article proposes a brief analysis of how the museums dedicated to the themes of slavery and slave trade in metropolitan France treat the subjects of slavery and slave trade as a part of the nation’s past.